Evaluasi Pelayanan Penumpang dan Kapal di Pelabuhan Penyeberangan Bajoe dengan Metode CSI (Customer Satisfaction Index): - - Alex, Juan Anugrah; Idris, Misliah; Djafar, Wihdat; Chairunnisa, Sitti; Djalante, Abdul Haris (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Bajoe Port is a crossing port located in Bone Regency, South Sulawesi which connects South Sulawesi Province with Southeast Sulawesi Province and Eastern Indonesia. This port is located in Tanete District, East Riattang with an area of 48.88 km2. This port has a strategic role in connecting maritime trade or community movement in Eastern Indonesia. As an interprovincial crossing port. Bajoe Port needs to build and develop port facilities by considering priority needs and funding capabilities in accordance with laws and regulations. This study aims to evaluate the availability and condition of the main and supporting facilities of Bajoe Port and analyze the performance of Bajoe Port services to passengers and ships. The analysis method used uses the CSI (Customer Satisfaction Index) method. This research was conducted by field survey to determine the availability and condition of basic and supporting facilities available at Bajoe Port. To measure the level of passenger satisfaction is carried out using interview methods and questionnaire measuring instruments distributed to respondents. Based on KM 52 of 2004, it is known that the availability and condition of basic and supporting facilities of Bajoe Port amounted to 63.63% of the available facilities. Based on PM 37 of 2015, it is known that the percentage of passenger satisfaction is above 80.55%. Keywords: Evaluation, Facilities, Services, CSI, Port